Research Design and Major Issues in Developing Dynamic Theories by Secondary Analysis of Qualitative Data - Bahadir K. Akcam; Senem Guney; Anthony M. Cresswell (Systems, 2019)
This article discusses the use of the Grounded Theory approach to the analysis of qualitative data to develop dynamic theories. The main objective of the article is to explore the major issues in bringing Grounded Theory and System Dynamics approaches together. The discussion employs an example of secondary analysis of qualitative data as a mixed-method research design for System Dynamics researchers. Findings from this example are organized in a table by research stages. Some of the reported major issues have divided researchers in their fields, such as the theoretical sensitivity issue in the Grounded Theory field and the qualitative and quantitative modeling issue in the System Dynamics field. Other major issues, such as the nature and richness of the dataset, can limit the data analysis and the research outputs. Researchers using the mixed-method should address these issues, and the present article offers solutions for them.